Cointegration and structural breaks in the PIIGS economies - Ferreira, N. (2017)
Due to the economic recession which started in 2008, several members of the European Union became historically known as PIIGS. These states include Portugal, Italy, Ireland, Greece and Spain and if ombined together, they form the acronym PIIGS. The reason why these countries were grouped together is the substantial instability of their economies, which was an evident problem in 2009. The reason why the five countries gained popularity is a serious concern within the EU, with regard to their national debts, especially for Greece. The latter country was involved in a controversial affair after allegedly falsifying its public financial data. In the year 2010, it was evident that the five states were in need of corrective action in order to regain their former financial stability. Because of the dirty farm animal associated with the acronym, several country leaders from the financially troubled countries have voiced out disagreement with the use of the term. However, there are quite a number of reporters and columnists who still refer to it when talking about the widespread economic crisis within the European Union. Although some prominent politicians have criticized the practice, the use of the word is very hard to shake off.